Kontribusi Kelincahan dan Kecepatan terhadap Kemampuan Hasil Mendribbling Bola pada Siswa yang Mengikuti Ekstrakulikuler Futsal SMP Insan Utama Pekanbaru - Muhammad Ridho; Hirja Hidayat; Alimandan (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2025)
To obtain the background of the problem, the researcher conducted direct observation at the research location at SMP Insan Utama Pekanbaru. According to initial observations, in futsal practice, the researcher found symptoms such as many students who were not yet able to achieve maximum futsal techniques, especially dribbling. This study aims to determine the contribution of agility and speed to the results of extracurricular football dribbling of SMP Insan Utama Pekanbaru students. In this study, a correlational research method was used, the population used was 20 students of SMP Insan Utama Pekanbaru. The statistical analysis used was the correlation technique. The research method used was correlation research with the population of SMP Insan Utama Pekanbaru students, which means that the contribution of agility and speed to the results of extracurricular football dribbling of SMP Insan Utama, Pekanbaru Regency was 41.08% while the rest was influenced by other factors. The test used in this study through the contribution test of the results of the first hypothesis test 0.641> r-table 0.444, the results of the second hypothesis 0.467> r-table 0.444 and the calculation results state that the calculated r value of 0.752 is greater than the r table of 0.444 with a level of 41.08%,